Fungos micorrízicos arbusculares e composto de água residuária da suinocultura no desenvolvimento de morangueiro de dia neutro - Welter, Paola Daiane (2018)
The strawberry is extremely demanding as to the physical and soil fertility conditions. The FMAS increase an area of root absorption, allowing greater absorption of water and nutrients, mainly phosphates. The swine wastewater compost and an organic compound concentrated in nutrients, promoting the increase of the pH, the available P and K levels and the soil micronutrients. The general objective of this work is to analyze the influence of different species of AMF and swine wastewater compost no development of neutral day strawberry plants. In this way they have carried out three experiments. The first objective defines efficient arbuscular mycorrhizal fungi for the development of strawberry plants of neutral day cultivars. In the second, the CARS was compared with different substrates formulated from bovine manure and vermicompost in the development of neutral day strawberry plants. The third one evaluated the effect of different AMF species and the application of CARS in the development of neutral day strawberry plants. Arbuscular mycorrhizal fungi have affinity with strawberry plants, especially the genus Acaulospora, which colonizes widely as plants both in the presence and absence of organic compound. The addition of the wastewater compost to soil, in general, provides the development of strawberry plants. The use of CARS as a substrate component raises the contents of the tissues of the plants, and their action is optimized in the presence of mycorrhizal fungi, being equivalent to a mineral fertilization.